Changes in hepatic volume and body composition following a two-week very low-calorie diet (VLCD) prior to a laparoscopic Nissen fundoplication - Francis-Mico Price; Francois Nicholaas Schutte (The South African Journal of Clinical Nutrition)
An enlarged fatty liver makes laparoscopic surgery of the upper gastrointestinal tract (GIT) more technically challenging. A 35-year-old female was referred to the dietitian for a preoperative very low-calorie diet (VLCD) to assist in decreasing hepatic volume and visceral adiposity. This case study highlights that the same benefits shown using preoperative VLCDs in bariatric patients as part of enhanced recovery after surgery (ERAS) guidelines can be observed in non-bariatric upper GIT surgery patients as well. In a time period of two weeks on a VLCD, a 50.7% reduction in left hepatic lobe volume (LHLV) was observed, as well as 1.4 kg fat loss around the abdomen.